2005
DOI: 10.1148/radiol.2353040726
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Effects of Ionic High-osmolar, Nonionic Monomeric, and Nonionic Iso-osmolar Dimeric Iodinated Contrast Media on Renal Tubular Cells in Vitro

Abstract: Besides hyperosmolality, direct cytotoxic effects of contrast media molecules contribute to their cytotoxic effects. Results of this study indicate that dimeric contrast media molecules have a greater potential for cytotoxic effects on proximal renal tubular cells in vitro than do monomeric contrast media molecules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
91
1
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(99 citation statements)
references
References 45 publications
3
91
1
4
Order By: Relevance
“…(D) (C) studies, 21,22 and also on the fact that ICM are concentrated in the kidneys compared with blood plasma. Urinary concentrations of ICM can be up to 50-100 times that in plasma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(D) (C) studies, 21,22 and also on the fact that ICM are concentrated in the kidneys compared with blood plasma. Urinary concentrations of ICM can be up to 50-100 times that in plasma.…”
Section: Discussionmentioning
confidence: 99%
“…Heinrich et al 21 compared different contrast media with the MTT assay, and when ICM were compared at equal iodine concentrations (75 mg I/mL), they found that dimeric contrast media showed a slightly weaker effect on inhibition of mitochondrial dehydrogenases than monomers, but this difference was not statistically significant. In the same study, the contrast media were also compared at molar basis and it was shown that dimeric ICM were significantly more cytotoxic than monomers on cultured renal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it cannot be excluded that gadodiamide also exerts a chemotoxic effect. Such effects may include non-osmolality dependent release of vasoconstrictors such as endothelin [12] and direct cytotoxic effects on tubular cells [35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…This early diuresis is essential and allows limiting the contact time of the contrast product with the nephrons, which is the main physiopathological mechanism of nephrotoxicity. PCI stasis in the renal tubular lumen is responsible for direct cell damage [20]. The degree of renal tubular cytotoxicity is directly related to the duration of exposure of these cells to the iodinated contrast agent.…”
Section: Discussionmentioning
confidence: 99%